Analisis Dialel untuk Pendugaan Parameter Genetik Komponen Hasil pada Cabai (Capsicum annuum L.) menggunakan Metode Hayman - Istiqlal, Muhammadl Ridha Alfarabi; Syukur, Muhamad; Wahyu, Yudiwanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThe diallel cross analysis method was developed to obtain genetic information involved in a population formed closely to Hardy-Wienberg equilibrium. The objective of this research was to study the genetic parameters on yield component of crossing on big and curly species of red pepper using Hayman approach for dialel cross-analysis method. This approach used 6 parental genotypes and 30 full-diallel cross combinations F1 hybrids. Appearance of the character was controlled by one up to two groups of positive additive genes. Each character observed has a partial dominance. Dominant genes were found much more in the parental characters of weight per plant (IPBC120), flesh thickness of fruit (IPBC2), fruit diameter (IPBC159), and fruit length (IPBC2). The broad sense heritability values on each character was high. Whereas, narrow sense heritability value for some characters were also high, except for character of weight per plant which were moderate.Keywords: additive effects, dominant effects, gene, heritability